Vibrationally excited HCN and outflows in (Ultra-) Luminous Infrared Galaxies - Hallqvist, Filippa (My University, 2017)
To understand what happens in galaxy nuclei and how central super-massive black holes (SMBHs) evolve and affect their surroundings is made very difficult by large masses of obscuring gas and dust, complicating observations at optical and infrared wavelengths. Instead, it has been suggest that HCN in its first vibrational state (HCN-VIB) is an excellent tracer of these deeply buried nuclei, making it possible to observe dynamics and temperatures of regions that would remain hidden at shorter wavelengths. The existence of HCN-VIB may also trace a period of rapid growth of the central SMBH, just before the onset of fast galactic outflows. However, the samples used to suggest this trend have so far been very small and any correlation would need to be statistically determined. The aim of this thesis is to explore if a correlation exists between the ratio of HCN-VIB line luminosity and the far infrared luminosity (L(HCN-VIB)/LFIR), and molecular outflows or inflows in (Ultra) Luminous Infrared Galaxies ((U)LIRGs). This is done by collecting observational data of the HCN-VIB line from the literature and comparing it to outflow and inflow velocities traced by OH absorption. To establish if a correlation exists, Fisher’s exact test is performed. As a case study, the vibrational temperature and mass is also estimated for the LIRG UGC 5101. We find that UGC 5101 has a vibrational temperature of Tvib = 442 K while the dynamical mass is estimated to Mdyn(r < 378 pc) = 5.6 × 1010 M. The dense gas mass is estimated to Mdense = 9.5 × 108 M. Finally, performing Fisher’s exact test on the sample of galaxies, a likely correlation between high L(HCN-VIB)/LFIR ratios and a lack of fast outflows is found.
Keywords: Fysik; Physical Sciences